Novel quinolines bearing a biologically active trimethoxyphenyl moiety as a new class of antitumor agents - Al-Said, Mansour S.; Bashandy, Mahmoud S.; Ghorab, Mostafa M. (Arzneimittelforschung, 2011)
The present paper describes the synthesis of some novel 2-amino-4-substituted aryl-5-oxo-1-(3,4,5-trimethoxy)-l,4,5,6,7,8-hexahydroquinoline-3-carbonitriles 6a–s starting with 3-(3,4,5-trimethoxyanilino)cyclohex-2-enone 3. All the newly synthesized compounds were evaluated for their in vitro antitumor activity. Compounds 6j, 6ρ and 6q showed higher activity with IC50 values 10, 10, 15 μg/mL, respectively, when compared with doxorubicin as a reference drug (IC50 value 37.5 μg/mL).
Keywords: Antitumor activity; Cyclohexane-l,3-dione; Quinoline derivatives; Synthesis; 3,4,5-Trimethoxyaniline